Impact of bruxism on craniomandibular morphology: A cone-beam computed tomographic study - Serafim, Irene [UNESP]; Rode, Sigmar [UNESP]; Lopes, Sérgio [UNESP]; Oliveira, Wagner [UNESP]; Pinho, Sérgio; Silva, Ertty [UNESP]; Winocur, Efraim; Meira E Cruz, Miguel (Taylor & Francis, 2022)
Objective: The main goal of this work was to address craniomorphological characteristics of patients with bruxism when compared to those without bruxism using cone beam computed tomography (CBCT) imaging. Methods: Seventy CBCT images of an equal number (n = 35) of orthodontic patients with and without bruxism (age range, 18–44 years) were retrospectively analyzed. Sagittal evaluation, mandibular shape, and skeletal asymmetry were systematically assessed in both groups. Results: Significant differences (p < 0.05) were observed between groups for Right Articular Fossa (AF)–Axial Plane (AP) and Left AF–AP (B > NB), Right Gonial Angle (GA), Left GA, Sella-Nasion and Occlusal Plane (B < NB). Age (13%), Condyle-Gonion (18%), AF to AP (67%), and Mental-AP (16%) had the greatest impact on bruxers. Conclusion: In this study, the CBCT 3D image showed significant differences in craniofacial morphology, particularly in the mandibular structure of bruxers compared with non-bruxers.
Keywords: bruxism; cone-beam computed tomography; facial morphology; Temporomandibular joint